2005
DOI: 10.2174/1566524053152825
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transcriptome Analysis in Pre-Clinical Toxicology

Abstract: A major benefit of the genomics revolution in biomedical research has been the establishment of transcriptome analysis as an enabling technology in the drug development process. Nowhere in the realm of drug development has the expectation of the impact of transcriptome analysis been greater than in the area of pre-clinical toxicology. Transcriptome analysis, along with other new high-content data generating technologies, has the potential to radically improve the drug safety assessment process by allowing drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Several studies have been reported using toxicogenomic techniques to examine tissue responses to toxicants [88][89][90] . Thus, now this technology is readily available it will be used more for this field of research in the near future.…”
Section: Toxicogenomicsmentioning
confidence: 99%
“…Several studies have been reported using toxicogenomic techniques to examine tissue responses to toxicants [88][89][90] . Thus, now this technology is readily available it will be used more for this field of research in the near future.…”
Section: Toxicogenomicsmentioning
confidence: 99%
“…Genomic data can be more sensitive and objective than traditional methods for the early prediction of compound-induced toxicity. Microarray expression profiling during preclinical drug development is expected to aid in uncovering unexpected or secondary pharmacology, predicting adverse effects, and understanding the mechanisms of drug action or toxicity (Battershill, 2005;Heinloth et al, 2004;Irwin et al, 2004;Searfoss et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, gene expression data (transcriptomics) are thought to be more sensitive than traditional toxicological endpoints (Searfoss et al, 2005). Toxicogenomics can also help to bridge traditional in vitro and in vivo toxicity assessment (Wilson et al, in press), and could be a very effective tool in studying the safety of herbal medicines by expanding the predictivity of potential toxicity in earlier stages of product development (Amir-Aslani, 2008; Blomme et al, 2009).…”
Section: Opportunities and Challengesmentioning
confidence: 99%